Endoscopic ultrasound safety and efficacy in pediatric pancreatobiliary and gastrointestinal disorders: single-center retrospective trial - Zhang, Jiayu; Deng, Zhaohui (Frontiers in Pediatrics, 2025)
BackgroundWhile endoscopic ultrasound (EUS) is well established as a standard diagnostic and therapeutic tool in adults, its use in children remains limited. This study assessed the indications, safety, and clinical impact of diagnostic and therapeutic EUS in children with pancreatobiliary and gastrointestinal disorders.MethodsWe retrospectively analyzed pediatric patients with pancreatobiliary and gastrointestinal disorders who underwent EUS at our institution between January 2022 and June 2025.ResultsFifty-three EUS procedures were conducted in children with a median age of 9.6 ± 3.0 years. Indications for EUS included acute recurrent pancreatitis (n = 15), suspected chronic pancreatitis (n = 12), suspected choledocholithiasis (n = 7), obstructive jaundice (n = 5), pancreatic mass (n = 1), gastric mucosal lesions (n = 6), suspected esophageal lymphoma recurrence (n = 1), suspected autoimmune hepatitis (n = 1) and pancreatic pseudocyst (PPC, n = 5). ERCP was performed during the same anesthesia for all children requiring it post-EUS. Five patients underwent cystogastrostomy for symptomatic PPC with 100% technical and clinical success. The efficacy of EUS in guiding definitive therapeutic decisions and invasive interventions was 100%. Notably, no major complications occurred.ConclusionEUS is safe and effective diagnostic and therapeutic modality in pediatric patients with pancreatobiliary and gastrointestinal disorders.